Polymer composite porous water-absorbing material and preparation method thereof

Through the preparation method of polymer composite porous water-absorbing materials, materials such as chitin, water-soluble urea-formaldehyde resin prepolymer and corn straw powder are used to solve the shortcomings of existing high-water-absorbing materials in terms of resource utilization and environmental protection, achieving efficient and environmentally friendly water absorption and water retention effects, and having sustained release properties.

CN119842111AActive Publication Date: 2025-04-18JILIN JIANZHU UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510075797.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Existing highly absorbent materials have shortcomings in resource utilization and environmental protection. For example, highly absorbent resins rely on non-renewable petroleum resources, starch-based materials are perishable and have poor water retention, and cellulose-based materials are complex in extraction and preparation and are not conducive to environmental protection.

Method used

Using a preparation method of polymer composite porous water-absorbing material, the water-absorbing material with a porous structure is formed by reacting and mixing materials such as chitin, water-soluble urea-formaldehyde resin prepolymer and corn straw powder during high-pressure liquefaction and foaming.

Benefits of technology

It realizes the preparation of polymer composite porous water-absorbing materials that are easy to obtain raw materials, simple process, green and environmentally friendly. It has high water absorption and high water retention, and can be decomposed into nutrients available to soil and plants after the water retention fails, and has sustained release properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842111A_ABST
    Figure CN119842111A_ABST
Patent Text Reader

Abstract

The invention provides a polymer composite porous water-absorbing material and a preparation method thereof, and belongs to the field of soil moisturizing and fertility increasing. The invention provides a preparation method of a polymer composite porous water-absorbing material, which comprises the following steps: firstly, pre-polymerizing formaldehyde and urea serving as raw materials through an acid-base catalyst to obtain a water-soluble urea-formaldehyde resin solution; a straw liquefied mixture, an animal protein foaming agent, a silicon resin polyether emulsion, a super absorbent resin aqueous solution, a modified chitin suspension and a polyvinyl formal solution are added, a high-magnification foaming system is obtained in a mechanical foaming mode, a proper amount of phosphoric acid is added, curing and drying are conducted, and the polymer composite porous water absorbing material is obtained. In the preparation process of the porous water absorption material, chemical and physical high crosslinking of urea resin, modified chitin, super absorbent resin, silicon resin polyether and polyvinyl formal is achieved, and the water absorption material is uniform in pore structure and high in pore, and has the advantages of being high in water absorption rate and high in repeated water absorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of straw resource recycling, and in particular relates to a polymer composite porous water-absorbing material and a preparation method thereof. Background Art

[0002] At present, super absorbent materials are generally classified into starch series, synthetic resin series, and cellulose series.

[0003] At present, the most widely used material is super absorbent resin (SAPs), because it can absorb thousands of times its own weight of water, has good water absorption and water retention capacity, and is widely used in disposable sanitary products, industry, agriculture, gardening, food and medical supplies. However, super absorbent resin is made by grafting copolymerization of acrylamide (Am) and acrylic acid (AA), and most of these cross-linking agents come from non-renewable petroleum resources. Starch-based absorbent materials have a wider source and are relatively cheap. They are a natural polyhydroxy substance, generally starch grafted with acrylate and acrylamide as the main means, but they also have some shortcomings, such as easy to rot and poor water retention.

[0004] In addition, cellulose-based water-absorbent materials have the characteristics of abundant sources, low prices, renewability, microbial degradation, safety and non-toxicity. However, the extraction and purification of cellulose raw materials also require a certain amount of energy consumption, and the preparation process is complicated, with a lot of intermediate waste, which is not conducive to environmental protection.

[0005] Therefore, there is an urgent need to provide a method for preparing a polymer composite porous water-absorbing material with easy-to-obtain raw materials, simple process, and green environmental protection, which can achieve resource recycling and can also prepare a moisturizing and fattening agent with high water absorption and high water retention. Summary of the invention

[0006] In view of the above problems existing in the prior art, the object of the present invention is to provide a polymer composite porous water-absorbing material.

[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a polymer composite porous water-absorbing material comprises the following steps:

[0009] Step 1: Place the formaldehyde solution in a reactor equipped with a condenser, a stirring blade and a thermometer, adjust the temperature to 50°C, and adjust the pH value to 8.5 with sodium hydroxide, add the first batch of urea to the reactor so that the molar ratio of formaldehyde to urea is 2.1, and react for 30 minutes;

[0010] Step 2: Add the second batch of urea to the reaction solution obtained in step 1, adjust the molar ratio of formaldehyde to the total of the two batches of urea added to 1.6, raise the temperature to 90° C., and react for 40 minutes;

[0011] Step 3: adjusting the pH of the reaction solution obtained in step 2 to 5.0 with phosphoric acid, and when the viscosity of the reaction solution reaches 0.25-0.40 Pa·s, adjusting the pH value to 8.5 with sodium hydroxide, reducing the temperature to 60° C., then adding the third batch of urea, adjusting the final molar ratio of formaldehyde to urea to 1.4, reacting for 10 minutes, and obtaining a water-soluble urea-formaldehyde resin prepolymer;

[0012] Step 4: Pour a certain amount of deionized water into the reactor, add a certain amount of urea and sodium hydroxide and stir evenly, add a certain amount of chitosan powder and disperse it in the reaction solution, precool it to -18°C, freeze it for 48 hours, and obtain a clear and transparent aqueous solution after thawing, add a certain amount of sodium chloroacetate, maintain the reaction solution at 15°C, react for 24 hours, and obtain a modified chitosan suspension;

[0013] Step 5: adding a certain amount of ethylene glycol and deionized water into a high-pressure reactor, adding a certain amount of corn straw powder and a certain amount of phosphoric acid catalyst and mixing them evenly, raising the temperature of the reaction liquid to 170° C. under nitrogen protection, reacting for 60 minutes, cooling to obtain a straw liquefied mixture, and then sequentially adding and mixing the chitosan suspension obtained in step 4 and the water-soluble urea-formaldehyde resin prepolymer obtained in step 3, adding and mixing evenly, and then adding a certain amount of silicone resin polyether emulsion and mixing evenly;

[0014] Step 6: Pour a certain amount of deionized water into a high-speed stirrer, add a certain amount of super absorbent resin powder, and stir at high speed to evenly disperse the super absorbent resin powder in the deionized water, then add the reaction solution obtained in step 5 and mix evenly;

[0015] Step 7: Pour a certain amount of deionized water into the reactor, add a certain amount of 17-99 polyvinyl alcohol, heat to 90°C, add a certain amount of hydrochloric acid solution when the polyvinyl alcohol is dissolved, adjust the pH value of the reaction solution to 2, add formaldehyde aqueous solution under stirring conditions, heat to 95°C, and immediately add sodium hydroxide aqueous solution after the reaction solution shows water separation, adjust the pH value of the reaction solution to 7, and stir at high speed to finally obtain a polyvinyl alcohol formal solution, and then add the polyvinyl alcohol formal solution to the mixed solution in step 6 and mix evenly;

[0016] Step 8: Pour a certain amount of deionized water into a high-speed stirrer, add a certain amount of foaming agent, and stir at high speed until the foam in the mixed liquid no longer increases, and then add it to the mixed liquid obtained in step 7 and mix evenly;

[0017] Step nine: uniformly mix the mixed solution obtained in step eight with a certain amount of phosphoric acid, and adjust the pH value of the mixed solution to 5;

[0018] Step 10: Stir the liquid obtained in step 9 and dry it at a certain temperature to obtain a foam water-absorbing material.

[0019] Furthermore, the formaldehyde content of the formaldehyde solution in step 1 is 37%.

[0020] Furthermore, the suspension in step 4 contains the following raw material components in parts by weight: 85 parts of water, 4 parts of urea, 11 parts of sodium hydroxide, 4 parts of chitosan powder, and 2.5 parts of sodium chloroacetate.

[0021] Furthermore, the ratio of ethylene glycol to water in the ethylene glycol aqueous solution in step five is 3:1, the mass ratio of ethylene glycol aqueous solution to straw powder is 2:1, the mass percentage of phosphoric acid catalyst to ethylene glycol aqueous solution is 1:10, and the mixed liquid contains the following raw material components in mass fractions: 10 to 20 parts of straw liquefaction mixture, 11 to 22 parts of modified chitosan suspension prepared in step four, 25 to 35 parts of water-soluble urea-formaldehyde resin prepolymer prepared in step three, and 2.5 parts of silicone resin polyether emulsion.

[0022] Furthermore, in step six, the super absorbent resin is a starch-acrylamide type super absorbent resin, and the mass percentage of the super absorbent resin water dispersion is 0.25%.

[0023] Furthermore, in step seven, the solid content of the polyvinyl alcohol aqueous solution is 10%, and the formaldehyde content is 2.5%.

[0024] Furthermore, the foaming agent in step eight is an animal protein foaming agent, and the mass percentage of the foaming agent aqueous solution is 3%.

[0025] Furthermore, the concentration of phosphoric acid in step nine is 2 mol / L.

[0026] Furthermore, the drying temperature in step 10 is 40-45° C., and the drying time is 20-30 hours.

[0027] A polymer composite porous water-absorbing material is prepared using any of the above-mentioned preparation methods.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The preparation method provided by the present invention has easy-to-obtain raw materials and a simple process. It can composite multiple polymers to improve the performance of porous materials. No intermediate waste is generated in the preparation process, which is more environmentally friendly and can achieve resource recycling. Moreover, the porous water-absorbing material prepared by the preparation method of the present invention will decompose into substances that can provide nutrients to soil and plants after the water retention property fails, so it also has a slow-release property and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the polymer composite porous water-absorbing material prepared by the preparation method of Example 1 of the present invention;

[0031] Figure 2 This is a scanning electron microscope image of the polymer composite porous water-absorbing material prepared by the preparation method of Example 2 of the present invention;

[0032] Figure 3 This is a scanning electron microscope image of the polymer composite porous water-absorbing material prepared by the preparation method of Example 3 of the present invention;

[0033] Figure 4 This is a scanning electron microscope image of the polymer composite porous water-absorbing material prepared by the preparation method of Example 4 of the present invention;

[0034] Figure 5 This is a scanning electron microscope image of the polymer composite porous water-absorbing material prepared by the preparation method of Example 5 of the present invention;

[0035] Figure 6 This is a scanning electron microscope image of the polymer composite porous water-absorbing material prepared by the preparation method of Example 6 of the present invention;

[0036] Figure 7 A water absorption curve diagram of the polymer composite porous water-absorbing material prepared by the preparation method of Example 6 of the present invention obtained by conducting a water absorption test;

[0037] Figure 8 This is a water retention rate curve diagram obtained by conducting a water retention test on the polymer composite porous water-absorbing material prepared by the preparation method of Example 6 of the present invention.

[0038] Fig. 9 This is a repeated liquid absorption curve diagram obtained by conducting a water retention test on the polymer composite porous water-absorbing material prepared by the preparation method of Example 6 of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with specific embodiments.

[0040] The invention mixes straw powder with ethylene glycol and phosphoric acid, and performs high-pressure liquefaction to obtain a partially liquefied straw fiber mixture.

[0041] In the present invention, the straw is obtained by pre-treating the straw raw material.

[0042] In the present invention, the pretreatment preferably includes: washing the straw raw material at room temperature, first drying in an 80°C oven, soaking in deionized water at room temperature for 10 hours, second drying in an 80°C oven, crushing and ball milling.

[0043] In the present invention, the crushing equipment is preferably a wall-breaking machine; the present invention has no special limitation on the operation of the wall-breaking machine, and the straw raw material can be crushed by an operation method well known to those skilled in the art.

[0044] In the present invention, the ball milling speed is preferably 250-350r / min, more preferably 300r / min; the ball milling time is 4-6h, more preferably 5h. The present invention can make the size of the obtained straw smaller by pre-treating the straw raw material, and the contact area with the phosphoric acid solution is larger when immersed in the liquefier, which is more conducive to fiber defibrination and separation of cellulose; at the same time, the straw can be suspended in the mixed liquid at a finer particle size, so that the water-absorbing and water-retaining material can be directly prepared without filtering, and no intermediate waste is generated in the preparation process, and the resource recycling is more sufficient, which is more green and environmentally friendly.

[0045] In the present invention, the particle size of the straw is 10 to 150 μm, preferably 20 to 130 μm, more preferably 50 to 100 μm, and most preferably 60 to 80 μm. The present invention controls the particle size of the straw within the above range, which is more conducive to the dissolution of cellulose and the generation of polyol substances, ensures that the straw powder with a micro-particle size can be stably suspended in the suspension, is more conducive to full contact with other components, thereby forming a water-absorbing and water-retaining material with uniform and rich pore structure, is more conducive to obtaining higher water absorption and water retention, and realizes the full recycling of the straw.

[0046] The present invention controls the mass ratio of straw to liquefier solution within the above range, which is more conducive to fiber defibrination and dissolution in the straw, thereby obtaining more polyol substances, thereby effectively improving the water absorption and water retention of the straw-based water absorbent and water retaining agent.

[0047] In the present invention, the straw is preferably a mixture of one or more of corn straw, wheat straw, soybean straw, sorghum straw, sunflower straw, peanut straw, rice straw, cotton straw and grass straw. The present invention not only facilitates the recycling of resources by selecting the above types of straw, but also ensures that the straw contains more abundant cellulose.

[0048] In the present invention, the liquefier can be a polar solvent such as ethylene glycol, propylene glycol, polyethylene glycol, vinyl propionate, etc., preferably ethylene glycol.

[0049] In the present invention, the liquefaction temperature is preferably 150-180°C, more preferably 165-175°C, and most preferably 170°C; the impregnation time is preferably 40-90 minutes, more preferably 50-70 minutes, and most preferably 60 minutes. By controlling the impregnation liquefaction temperature and time within the above ranges, the pretreated straw can be defibrated and cellulose can be swollen under the action of heat, and a large amount of polyols can be generated by reaction.

[0050] The present invention allows the cellulose in the straw to fully react with the liquefier, so that the cellulose is combined with more active functional groups, which is more conducive to cross-linking with the products formed by the subsequent polycondensation reaction into a rich three-dimensional network structure, thereby obtaining a larger specific surface area, and thus having stronger water absorption and water retention.

[0051] In the present invention, the foaming agent is preferably a mixed solution of an animal protein foaming agent and deionized water.

[0052] In the present invention, the foaming agent is preferably prepared by stirring and foaming the animal protein foaming agent and deionized water. The present invention has no special limitation on the stirring and foaming operation, and the foaming agent can be stirred until the foam is uniform and fine by using the stirring and foaming operation well known to those skilled in the art.

[0053] In the present invention, the catalyst is preferably phosphoric acid, hydrochloric acid or sulfuric acid, preferably phosphoric acid. By selecting the catalyst of the above acidic substance, the present invention can make the polycondensation reaction system in an acidic condition, which is more conducive to the full progress of the polycondensation reaction; at the same time, by selecting the above acidic type of catalyst, it can be beneficial to the use of water-absorbing and water-retaining materials in the soil, and the above type of catalyst can also slowly release substances that are beneficial to the soil after the water-absorbing material fails, which is more suitable for crops to absorb.

[0054] In the present invention, the pH value of the foam curing polycondensation reaction is preferably 2 to 6, more preferably 5.0.

[0055] In the present invention, the pH is preferably controlled by dropping a catalyst.

[0056] In the present invention, the drying temperature is preferably 55-65°C, more preferably 60°C; the drying time is preferably 20-30h, more preferably 24-28h. The present invention is more conducive to the full cross-linking of urea-formaldehyde resin and other polymer substances by controlling the temperature and time of curing and drying, making the three-dimensional spatial network in the water-absorbing and water-retaining agent more complete and the pores more abundant, thereby effectively improving the water absorption and water retention effect of the polymer composite porous water-absorbing material.

[0057] In the present invention, the drying step preferably further includes baking after the drying step is completed; the drying temperature is preferably 70-80°C, more preferably 80°C; the present invention has no special limitation on the drying time, as long as the drying state can be reached at the drying temperature.

[0058] The preparation method provided by the invention has easy-to-obtain raw materials, a simple process, is more environmentally friendly, and can realize resource recycling.

[0059] The present invention also provides a polymer composite porous water-absorbing material prepared by the preparation method described in the above technical solution.

[0060] The polymer composite porous water-absorbing material obtained by the preparation method provided by the present invention has excellent water absorption and water retention, and can be decomposed into substances that can provide nutrients for soil and plants after the water retention fails, so it also has slow-release performance and has good application prospects.

[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] A method for preparing a polymer composite porous water-absorbing material comprises the following steps:

[0064] Step 1: placing the formaldehyde solution in a reactor equipped with a condenser, a stirring paddle and a thermometer, adjusting the temperature to 50°C, and adjusting the pH value to 8.5 with sodium hydroxide, adding the first batch of urea to the reactor so that the molar ratio of formaldehyde to urea is 2.1, and reacting for 30 minutes, wherein the concentration of the formaldehyde solution is 37%, a total of 70 parts are added, and 24 parts of the first batch of urea are added so that the molar ratio of formaldehyde to urea (F / U1) is 2.1;

[0065] Step 2: Add the second batch of urea to the reaction solution obtained in step 1, adjust the molar ratio of formaldehyde to the total of two batches of urea added to 1.6, raise the temperature to 90°C, and react for 40 minutes, wherein the amount of the second batch of urea added is 8 parts, and adjust F / (U1+U2) to 1.6;

[0066] Step 3: The reaction solution obtained in step 2 is adjusted to pH 5.0 with phosphoric acid. When the viscosity of the reaction solution reaches 0.25-0.40 Pa·s, the pH value is adjusted to 8.5 with sodium hydroxide, and the temperature is reduced to 60°C. Then, the third batch of urea is added to adjust the final molar ratio of formaldehyde to urea to 1.4, and the reaction is carried out for 10 minutes to obtain a water-soluble urea-formaldehyde resin prepolymer, wherein the amount of the third batch of urea added is 4.5 parts, and the final F / (U1+U2+U3) is adjusted to 1.4;

[0067] Step 4: Pour a certain amount of deionized water into the reactor, add a certain amount of urea and sodium hydroxide and stir evenly, add a certain amount of chitosan powder and disperse it in the reaction solution, precool it to -18°C, freeze it for 48 hours, and obtain a clear and transparent aqueous solution after thawing, add a certain amount of sodium chloroacetate, maintain the reaction solution at 15°C, react for 24 hours, and obtain a modified chitosan suspension, wherein the amount of deionized water added is 85 parts, the amount of urea added is 4 parts, the amount of sodium hydroxide added is 11 parts, and the amount of chitosan powder added is 4 parts;

[0068] Step 5: adding a certain amount of ethylene glycol and deionized water to a high-pressure reactor, adding a certain amount of corn stalk powder and a certain amount of phosphoric acid catalyst and mixing evenly, raising the temperature of the reaction solution to 170°C under nitrogen protection, reacting for 60 minutes, cooling to obtain a straw liquefied mixture, and then sequentially adding and mixing the chitosan suspension obtained in step 4 and the water-soluble urea-formaldehyde resin prepolymer obtained in step 3, adding and mixing evenly, and then adding a certain amount of silicone resin polyether emulsion and mixing evenly, wherein the amount of ethylene glycol added is 15 parts, the amount of deionized water added is 5 parts, the amount of corn stalk powder added is 10 parts, the amount of phosphoric acid catalyst added is 1 part, the straw liquefied mixture added during the mixing process is 10 parts, the modified chitosan suspension added is 11 parts, the water-soluble urea-formaldehyde resin prepolymer added is 25 parts, and the silicone resin polyether emulsion added is 2.5 parts;

[0069] Step 6: Pour a certain amount of deionized water into a high-speed stirrer, add a certain amount of super absorbent resin powder, and stir at high speed to evenly disperse the super absorbent resin powder in the deionized water, then add the reaction solution obtained in step 5 and mix evenly, wherein the amount of deionized water added is 80 parts, and the super absorbent resin powder is a starch-acrylamide type super absorbent resin, and the amount added is 0.2 parts;

[0070] Step 7: pour a certain amount of deionized water into the reactor, add a certain amount of 17-99 polyvinyl alcohol, heat to 90°C, add a certain amount of hydrochloric acid solution when the polyvinyl alcohol is dissolved, adjust the pH value of the reaction solution to 2, add formaldehyde aqueous solution under stirring, heat to 95°C, add sodium hydroxide aqueous solution immediately after the reaction solution shows water separation, adjust the pH value of the reaction solution to 7, and stir at high speed to finally obtain a polyvinyl alcohol formal solution, then add the polyvinyl alcohol formal solution to the mixed solution in step 6 and mix evenly, wherein the amount of deionized water added is 83 parts, the amount of 17-99 polyvinyl alcohol added is 10 parts, the formaldehyde aqueous solution is a formaldehyde aqueous solution with a concentration of 37%, and the amount of formaldehyde aqueous solution added is 7 parts, and when the obtained polyvinyl alcohol formal solution is added to the mixed solution in step 6, the amount of polyvinyl alcohol formal solution added to the mixed solution is 10 parts;

[0071] Step 8: Pour a certain amount of deionized water into a high-speed stirrer, add a certain amount of foaming agent, and stir at high speed until the foam in the mixed solution no longer increases, and then add it to the mixed solution obtained in step 7 and mix evenly, wherein the amount of deionized water added is 18 parts, and the foaming agent is an animal protein foaming agent, and the amount of added is 2 parts;

[0072] Step nine: uniformly mix the mixed solution obtained in step eight with a certain amount of phosphoric acid, and adjust the pH value of the mixed solution to 5, wherein the concentration of phosphoric acid is 2 mol / L, and the amount added is 3 parts;

[0073] Step 10: Stir the liquid obtained in step 9 and dry it at a certain temperature to obtain a foam absorbent material, wherein the drying temperature is 40-45° C. and the drying time is 20-30 hours.

[0074] Example 2

[0075] The preparation method of this embodiment is basically the same as the preparation method of Example 1, except that, during the mixing in step five, 35 parts of water-soluble urea-formaldehyde resin prepolymer, 20 parts of straw liquefaction mixture, 22 parts of modified chitosan suspension, and 20 parts of polyvinyl formal solution are added, and the foam absorbent material is obtained through the subsequent same steps.

[0076] Example 3

[0077] The preparation method of this embodiment is basically the same as the preparation method of Example 1, except that, during the mixing in step five, 30 parts of water-soluble urea-formaldehyde resin prepolymer, 15 parts of straw liquefaction mixture, 16.5 parts of modified chitin suspension, and 15 parts of polyvinyl formal solution are added, and the foam absorbent material is obtained through subsequent identical steps.

[0078] Example 4

[0079] The preparation method of this embodiment is basically the same as the preparation method of Example 1, except that 27 parts of deionized water and 3 parts of foaming agent are added in step eight, and the foam absorbent material is obtained through the subsequent same steps.

[0080] Example 5

[0081] The preparation method of this embodiment is basically the same as the preparation method of Example 2, except that 27 parts of deionized water and 3 parts of foaming agent are added in step eight, and the foam absorbent material is obtained through the subsequent same steps.

[0082] Example 6

[0083] The preparation method of this embodiment is basically the same as the preparation method of Example 3, except that 27 parts of deionized water and 3 parts of foaming agent are added in step eight, and the foam absorbent material is obtained through the subsequent same steps.

[0084] The polymer composite porous water-absorbing materials prepared in Examples 1 to 6 were observed by scanning electron microscopy, wherein the scanning electron microscope photographs are as follows: Figures 1 to 6 shown.

[0085] according to Figure 1-3 It can be seen that the structure of the polymer composite porous water-absorbing material prepared in Examples 1-3 is relatively dense;

[0086] according to Figure 1 It can be seen that if the amount of straw liquefied mixture and urea-formaldehyde prepolymer is too little, the system strength is low, the pores are seriously damaged, and the bubble collapse phenomenon is serious, which affects the various properties of the polymer composite porous water-absorbing material.

[0087] according to Figure 2 It can be seen that the excessive amount of straw liquefied mixture and urea-formaldehyde prepolymer makes the structure of the polymer composite porous water-absorbing material dense, inhibits the formation of holes, and has fewer holes, which is not conducive to water absorption;

[0088] according to Figure 3 It can be seen that the network structure of the polymer composite porous water-absorbing material is relatively uniform, with many holes and the shapes and sizes of the holes are relatively uniform.

[0089] It can be seen that the porous structure of the polymer composite porous water-absorbing material prepared in Example 3 is the best.

[0090] According to 4 to 6, the network structure of the polymer composite porous water-absorbing material prepared in Examples 4 to 6 is more delicate and compact than that in Examples 1 to 3, with complete pore walls, uniform and moderate pore sizes, and more connected pores;

[0091] It can be seen that the porous structure of the polymer composite porous water-absorbing material prepared in Example 6 is the best.

[0092] The polymer composite porous water-absorbing materials prepared in Examples 1 to 6 were tested for water absorption by natural filtration method; wherein the absorbed water was selected from deionized water, tap water and 0.9wt.% NaCl solution; the water absorption multiple represents the amount of water absorbed, represented by the symbol W, in units of g / g, and the specific calculation formula is as follows:

[0093]

[0094] In the formula,

[0095] W: water absorption multiple, unit is g / g;

[0096] Wt: the mass of the polymer composite porous water-absorbing material after absorbing liquid, in g;

[0097] Wd: mass of the polymer composite porous water-absorbing material in dry state, in g;

[0098] The test results are shown in Table 1 and Figure 7 The water absorption capacity shown;

[0099]

[0100] Table 1

[0101] Among them, the absorption multiple of deionized water is represented by W1, the absorption multiple of tap water is represented by W2, and the absorption multiple of 0.9wt.% NaCl solution is represented by W3.

[0102] The polymer composite porous water-absorbing material after the water absorption test of the above Examples 1 to 6 was subjected to a water retention test. The test results are as follows: Figure 7 shown.

[0103] From Table 1 and Figure 7 It can be seen that the water-absorbing and water-retaining agents prepared in Examples 1 to 6 absorb deionized water at a rate of 12.65 to 26.68 g / g, tap water at a rate of 8.10 to 17.87 g / g, and 0.9 wt.% NaCl solution at a rate of 7.15 to 13.56 g / g within 48 hours. Among them, Example 6 has the best water absorption.

[0104] Figure 8 This is a water retention rate curve diagram obtained by conducting a water retention test on the polymer composite porous water-absorbing material prepared by the preparation method of Example 6.

[0105] Fig. 9 This is a repeated liquid absorption curve diagram obtained by conducting a water retention test on the polymer composite porous water-absorbing material prepared by the preparation method of Example 6.

[0106] Depend on Figure 8It can be seen that the water-absorbing and water-retaining agent prepared in Example 6 can retain water for 25 days after absorbing deionized water, can retain water for 23 days after absorbing tap water, and can retain water for 19 days after absorbing 0.9 wt.% NaCl solution.

[0107] Depend on Fig. 9 It can be seen that the water-absorbing and water-retaining agent prepared in Example 6 can still maintain a water absorption rate of more than 60% even if the water absorption is repeated 10 times during the repeated water absorption test.

[0108] The results of the embodiment show that the polymer composite porous water-absorbing material prepared by the preparation method provided by the present invention has a deionized water absorption rate of 26.68 g / g, a tap water absorption rate of 17.87 g / g, and a 0.9wt.% NaCl solution absorption rate of 13.56 g / g; the water retention time after absorbing deionized water can reach 25 days, the water retention time after absorbing tap water can reach 23 days, and the water retention rate after absorbing 0.9% NaCl solution can reach 19 days, and due to the complete three-dimensional spatial network in the water-absorbing and water-retaining material, the pores are more abundant, and due to the addition of the foaming agent, the specific surface area of ​​the water-absorbing and water-retaining agent is further increased, thereby further improving the water absorption and water retention of the water-absorbing and water-retaining material, so that the polymer composite porous water-absorbing material has a slow-release function of various fertilizers such as nitrogen, phosphorus and potassium.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a polymer composite porous water-absorbing material, characterized in that: The following steps are involved: Step 1: Place the formaldehyde solution in a reactor equipped with a condenser, a stirring blade and a thermometer, adjust the temperature to 50°C, and adjust the pH value to 8.5 with sodium hydroxide, add the first batch of urea to the reactor so that the molar ratio of formaldehyde to urea is 2.1, and react for 30 minutes; Step 2: Add the second batch of urea to the reaction solution obtained in step 1, adjust the molar ratio of formaldehyde to the total of the two batches of urea added to 1.6, raise the temperature to 90° C., and react for 40 minutes; Step 3: adjusting the pH of the reaction solution obtained in step 2 to 5.0 with phosphoric acid, and when the viscosity of the reaction solution reaches 0.25-0.40 Pa·s, adjusting the pH value to 8.5 with sodium hydroxide, reducing the temperature to 60° C., then adding the third batch of urea, adjusting the final molar ratio of formaldehyde to urea to 1.4, reacting for 10 minutes, and obtaining a water-soluble urea-formaldehyde resin prepolymer; Step 4: Pour a certain amount of deionized water into the reactor, add a certain amount of urea and sodium hydroxide and stir evenly, add a certain amount of chitosan powder and disperse it in the reaction solution, precool it to -18°C, freeze it for 48 hours, and obtain a clear and transparent aqueous solution after thawing, add a certain amount of sodium chloroacetate, maintain the reaction solution at 15°C, react for 24 hours, and obtain a modified chitosan suspension; Step 5: adding a certain amount of ethylene glycol and deionized water into a high-pressure reactor, adding a certain amount of corn straw powder and a certain amount of phosphoric acid catalyst and mixing them evenly, raising the temperature of the reaction liquid to 170° C. under nitrogen protection, reacting for 60 minutes, cooling to obtain a straw liquefied mixture, and then sequentially adding and mixing the chitosan suspension obtained in step 4 and the water-soluble urea-formaldehyde resin prepolymer obtained in step 3, adding and mixing evenly, and then adding a certain amount of silicone resin polyether emulsion and mixing evenly; Step 6: Pour a certain amount of deionized water into a high-speed stirrer, add a certain amount of super absorbent resin powder, and stir at high speed to evenly disperse the super absorbent resin powder in the deionized water, then add the reaction solution obtained in step 5 and mix evenly; Step 7: Pour a certain amount of deionized water into the reactor, add a certain amount of 17-99 polyvinyl alcohol, heat to 90°C, add a certain amount of hydrochloric acid solution when the polyvinyl alcohol is dissolved, adjust the pH value of the reaction solution to 2, add formaldehyde aqueous solution under stirring conditions, heat to 95°C, and immediately add sodium hydroxide aqueous solution after the reaction solution shows water separation, adjust the pH value of the reaction solution to 7, and stir at high speed to finally obtain a polyvinyl alcohol formal solution, and then add the polyvinyl alcohol formal solution to the mixed solution in step 6 and mix evenly; Step 8: Pour a certain amount of deionized water into a high-speed stirrer, add a certain amount of foaming agent, and stir at high speed until the foam in the mixed liquid no longer increases, and then add it to the mixed liquid obtained in step 7 and mix evenly; Step nine: uniformly mix the mixed solution obtained in step eight with a certain amount of phosphoric acid, and adjust the pH value of the mixed solution to 5; Step 10: Stir the liquid obtained in step 9 and dry it at a certain temperature to obtain a foam water-absorbing material.

2. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: The formaldehyde content of the formaldehyde solution in step 1 is 37%.

3. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: The suspension in step 4 comprises the following raw material components in parts by weight: 85 parts of water, 4 parts of urea, 11 parts of sodium hydroxide, 4 parts of chitosan powder, and 2.5 parts of sodium chloroacetate.

4. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: The ratio of ethylene glycol to water in the ethylene glycol aqueous solution in the step five is 3:1, the mass ratio of the ethylene glycol aqueous solution to the straw powder is 2:1, the mass percentage of the phosphoric acid catalyst to the ethylene glycol aqueous solution is 1:10, and the mixed liquid contains the following raw material components in mass fractions: 10 to 20 parts of the straw liquefaction mixture, 11 to 22 parts of the modified chitosan suspension prepared in the step four, 25 to 35 parts of the water-soluble urea-formaldehyde resin prepolymer prepared in the step three, and 2.5 parts of the silicone resin polyether emulsion.

5. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: In the step 6, the super absorbent resin is a starch-acrylamide type super absorbent resin, and the mass percentage of the super absorbent resin water dispersion is 0.25%.

6. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: In the step 7, the solid content of the polyvinyl alcohol aqueous solution is 10%, and the formaldehyde content is 2.5%.

7. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: The foaming agent in step eight is an animal protein foaming agent, and the mass percentage of the foaming agent aqueous solution is 3%.

8. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: The phosphoric acid concentration in step nine is 2 mol / L.

9. The method for preparing a polymer composite porous water-absorbing material according to claim 1, characterized in that: The drying temperature in step 10 is 40-45° C., and the drying time is 20-30 hours.

10. A polymer composite porous water-absorbing material, characterized in that: The preparation is carried out using the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of straw composite super absorbent resin

    CN102838714A

  • Preparation method of straw-based super absorbent resin with nitrogen phosphorus fertilizer slow-release function

    CN104072686A

  • Cornstalk / chitin compound hemostatic sponge and preparation method and application thereof

    CN110420346A

  • Carboxymethyl chitin porous granular material as well as preparation method and application thereof

    CN111378200A

  • Straw-based water-absorbing and water-retaining agent and preparation method thereof

    CN114106841A